Tantangan etika dalam profesi pendidikan - Abrory, Makhtum Yandi (Maliki Interdisciplinary Journal, 2024)
The role and responsibilities of teachers have a significant impact on character formation and moral development of students. In this context, this research explores the primary role of teachers in instilling ethical values in their students. Through a qualitative approach, data was collected through interviews with teachers from various levels of education. The analysis shows that the teacher’s role is not only limited to conveying lesson material, but also as a model that forms ethical behavior patterns for students. Teachers are responsible for facilitating learning that promotes justice, respects diversity, and develops students’ moral awareness. This responsibility leads teachers to face various challenges, including balancing academic duties and character building, overcoming ethical dilemmas in teaching, and facilitating discussions on controversial issues. The findings of this research emphasize the importance of equipping teachers with the knowledge and skills necessary to become agents of moral change in educational environments. In addition, the results of this research also provide a basis for developing training and professional development programs that strengthen teachers’ ethical competence. Thus, this research has relevant implications in improving the quality of education and forming an ethical generation.